2005
DOI: 10.1590/s0085-56262005000200009
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of aedine mosquito species (Diptera, Culicidae, Aedini) occurring in Middle and South America (south of the United States) reflecting current generic and subgeneric status

Abstract: ABSTRACT. Checklist of aedine mosquito species (Diptera, Culicidae, Aedini) occurring in Middle and South America (south of the United States) reflecting current generic and subgeneric status. A list of species of tribe Aedini from Middle and South American, south of the United States, with their current generic combinations is provided. Its purpose is to enable entomologists, public health personnel and mosquito control workers to more quickly become familiar with recent formal taxonomic changes within the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
1
Order By: Relevance
“…Distribution of Ps. champerico includes Central America, northern part of South America and Amazon region (Lane 1992;Reinert et al 2005). This is the first report of the species in Atlantic forest, near the southern limit of the bioma, indicating underestimation of its distribution (Tabarelli et al 2005).…”
Section: Resultsmentioning
confidence: 89%
“…Distribution of Ps. champerico includes Central America, northern part of South America and Amazon region (Lane 1992;Reinert et al 2005). This is the first report of the species in Atlantic forest, near the southern limit of the bioma, indicating underestimation of its distribution (Tabarelli et al 2005).…”
Section: Resultsmentioning
confidence: 89%
“…Revised systematic checklist of 179 species of Ecuadorian Culicidae. Species listed include those published since the last major revision of world taxa by Knight and Stone (1977) ( Knight 1978 , Faran 1979 , Heinemann & Belkin 1979 , Sirivanakarn 1979 , Zavortink 1979a , b , Berlin & Belkin 1980 , Ward 1984 , Forattini & Sallum 1989 , Hall et al 1999 , Sallum & Hutchings 2003 , Reinert et al 2004 , 2005 , 2006 , 2008 , 2009 , Rueda et al 2004 , Harbach & Howard 2007 , Zavortink & Chaverri 2009 , González et al 2010 , Harrison et al 2012 , Ruiz-Lopez et al 2013 ). Species identified in this study are underlined; those underlined and in boldface comprise 37 new additions to the mosquito records from Ecuador.…”
Section: Supplementary Datamentioning
confidence: 99%
“…The 12 new species determined in this study are indicated. The classification used here follows that of Zavortink ( 1979a , b ), Reinert et al ( 2004 , 2005 , 2006 , 2008 , 2009 ) and Harbach and Howard (2007) .…”
Section: Supplementary Datamentioning
confidence: 99%
“…Infelizmente, a compilação e publicação de listas de espécies geralmente são consideradas de pouca importância e pouco atraentes (Cranston 2005). Entretanto, a informação fornecida pelos checklists e listas de fauna auxilia em diversos aspectos da entomologia aplicada, como em epidemiologia, e no manejo e controle de pestes/vetores (Civelek 2003, Reinert et al 2005.…”
Section: Introductionunclassified